Impact of Mild Behavioral Impairment on Longitudinal Changes in Cognition - Rouse, Hillary J; Ismail, Zahinoor; Andel, Ross; Molinari, Victor A; Schinka, John A; Small, Brent J (The journals of gerontology. Series A, Biological sciences and medical sciences, 2024)
BACKGROUND: To examine cross-sectional differences and longitudinal changes in cognitive performance based on the presence of mild behavioral impairment (MBI) among older adults who are cognitively healthy or have mild cognitive impairment (MCI). METHODS: Secondary data analysis of participants (n = 17 291) who were cognitively healthy (n = 11 771) or diagnosed with MCI (n = 5 520) from the National Alzheimer's Coordinating Center database. Overall, 24.7% of the sample met the criteria for MBI. Cognition was examined through a neuropsychological battery that assessed attention, episodic memory, executive function, language, visuospatial ability, and processing speed. RESULTS: Older adults with MBI, regardless of whether they were cognitively healthy or diagnosed with MCI, performed significantly worse at baseline on tasks for attention, episodic memory, executive function, language, and processing speed and exhibited greater longitudinal declines on tasks of attention, episodic memory, language, and processing speed. Cognitively healthy older adults with MBI performed significantly worse than those who were cognitively healthy without MBI on tasks of visuospatial ability at baseline and on tasks of processing speed across time. Older adults with MCI and MBI performed significantly worse than those with only MCI on executive function at baseline and visuospatial ability and processing speed tasks across time. CONCLUSIONS: This study found evidence that MBI is related to poorer cognitive performance cross-sectionally and longitudinally. Additionally, those with MBI and MCI performed worse across multiple tasks of cognition both cross-sectionally and across time. These results provide support for MBI being uniquely associated with different aspects of cognition.
Keywords: kognitivní dysfunkce; epizodická paměť; Cognition; kognice; neuropsychologické testy; Executive Function; lidé; senioři; Cognitive Dysfunction; Cross-Sectional Studies; exekutivní funkce; Aged; Neuropsychological Tests; Memory, Episodic; průřezové studie; Humans